제습기 성능분석을 위한 선형화 모델 및 해석해의 검증 - 이길봉; 이대영; 김민수 (대한설비공학회, 2004)
A silica gel desiccant dehumidifier is studied theoretically in this paper adopting several linearization assumptions. The governing equations are linearized with the assumptions, and the exact solutions to the temperature and the humidity ratio are obtained. In spite of the assumptions, the theoretical results are found to agree well with those from the numerical analysis without any assumption. In typical operation ranges of the desiccant dehumidifier, the time-averaged errors in the process air temperature and humidity ratio are less than 4% and 7%, respectively, and the corresponding root-mean-square values are less than 5% and 15%, respectively. The analytical solutions are expected to contribute to the fundamental understanding of the dehumidification and regeneration processes and the correlation analysis of the numerous parameters influencing the dehumidifier operation.